(untitled) - Twain, Mark (New York, NY, 1984)
This book give an incredible insight into the way life was actually lived all western Europe and the middle east in the 1800s. Other parts give testament to Twain's incredibly casual bigotry and racism and intolerance. But in one page he'll note his desire to not appear ignorant in front of a freed slave acting as tour guide in Venice; and then widely compliment the fellow for his intelligence and manner
Keywords: American literature,American fiction; 19th century,19th century